'A Billion Dollar Racket': the United States, South Vietnam, and Global Currency Manipulation during War, 1968–9. Issue 4 (7th August 2016) - Pho, Helen N.
ABSTRACT: While most historians have discussed corruption as a key factor leading to South Vietnam's downfall, they have not fully analysed the US and international dimensions of South Vietnamese corruption. This article argues that economic, political, and diplomatic circumstances of the Vietnam War encouraged widespread US participation in currency manipulation, an economically destructive form of corruption that had serious implications for the stability of the South Vietnamese state. The US inability to shape South Vietnam's setting of the official exchange rate allowed South Vietnam to overvalue the piaster at the cost of US taxpayers. Combined with the structural economic problems produced by the war, such as inflation, the favourable exchange rate encouraged Americans, Vietnamese, Indians, Chinese, Koreans, and other internationals to make quick profits through illegal transactions. From bookstores in Saigon to banks in Hong Kong, Dubai, and New York, currency manipulation involved a host of individuals and organisations around the globe. Although many critics of the war cited South Vietnamese corruption in their arguments for US withdrawal, congressional investigation into currency manipulation revealed that without the direct contributions of US soldiers and civilians, the magnitude of illegal economic transactions would not have existed as it did.